P.060 Time to treatment effect in Spinal Muscular Atrophy Type 1 (SMA1): an indirect comparison of treatments. (June 2019) - Finkel, RS; Dabbous, O; Arjunji, R; Droege, M; Feltner, DE; Novack, A; Menier, M; Sproule, DM
Abstract : Background: SMA1 is a rapidly progressing disease resulting in death/permanent ventilation by 2 years. This study compared clinical trial data evaluating the relationship between treatment timing, time to treatment effect, and clinical outcomes in SMA1 patients Methods: A post-hoc indirect treatment comparison was conducted to measure time-to-effect differences in AVXS-101 (CL-101, NCT02122952, cohort 2) vs nusinersen (ENDEAR, NCT02193074) or risdiplam (FIREFISH, NCT02913482) using CHOP-INTEND scores. Results: Compared with nusinersen, AVXS-101 more rapidly increased mean CHOP-INTEND score from baseline (9.8- and 14.9-point increase at 1- and 2-months post-AVXS-101 vs ≤5-point increase at 2-months post-nusinersen). Greater survival benefits and lower rates of permanent ventilatory support were also observed in AVXS-101- vs nusinersen-treated patients. Compared with risdiplam treatment, AVXS-101 improved median CHOP-INTEND scores (14.0-point increase at 2-months post-AVXS-101 vs 5.5-point increase at ~2-months post-risdiplam). Treatment differences were maintained through 8-months with additional improvements at all time-points. Conclusions: Although patients in these 3 cohorts are not entirely matched (e.g. age, disease severity), useful comparisons can still be made. Based on CHOP-INTEND scores, the treatment effect of AVXS-101 appears to be more rapid vs nusinersen or risdiplam. These findings suggest that timely restoration of SMN protein may be essential for maximizing outcomes in SMA1 patients.